Reinterpretation of KH. Hasyim Asy’ari’s Educational Jihad for Strengthening Youth Resilience in the Globalization Era - Niken Juliani; Ririn Isnadia; Herlini Puspika Sari (MANAGIERE: Journal of Islamic Educational Management, 2025)
This study analyzes KH. Hasyim Asy’ari’s concept of Educational Jihad as a strategic response to moral erosion and identity crises among youth in the era of globalization—a gap rarely addressed in previous Islamic education studies. Using a qualitative library research method and content analysis of Adabul ‘Alim wal Muta’allim and related literature, this research finds that Educational Jihad should be reinterpreted as a form of Contemporary Great Jihad encompassing intellectual, moral, and national dimensions. The key findings highlight three core implementations: strengthening learning ethics and teacher respect, integrating religious and scientific knowledge, and developing a pioneering spirit (Jihad Amaliyah). The novelty lies in formulating Educational Jihad as an integrated educational framework that reinforces resilience, character ethics, and national identity. Practically, this model contributes to shaping a generation that is intellectually competent, morally grounded, and adaptive to global challenges. Penelitian ini menganalisis konsep Jihad Pendidikan KH. Hasyim Asy’ari sebagai respons strategis terhadap erosi moral dan krisis identitas generasi muda di era globalisasi—sebuah kesenjangan yang jarang dibahas dalam studi pendidikan Islam sebelumnya. Menggunakan metode penelitian kualitatif jenis studi pustaka dengan analisis konten terhadap Adabul ‘Alim wal Muta’allim dan literatur terkait, penelitian ini menemukan bahwa Jihad Pendidikan perlu ditafsirkan sebagai Jihad Akbar Kontemporer yang mencakup dimensi intelektual, moral, dan kebangsaan. Temuan utama menunjukkan tiga implementasi: penguatan etika belajar dan penghormatan terhadap guru, integrasi ilmu agama dan sains, serta pengembangan semangat kepeloporan (Jihad Amaliyah). Kebaruan penelitian ini terletak pada formulasi Jihad Pendidikan sebagai kerangka pendidikan terpadu yang memperkuat ketahanan moral, etika karakter, dan identitas kebangsaan. Secara praktis, model ini berkontribusi membentuk generasi yang cerdas, berakhlak, dan adaptif terhadap tantangan global.